Relative study of steering protocols in delay tolerant network. Issue 4 (4th July 2017) - Gupta, Shaurya; Poonia, Ramesh C.; Gao, X. Z.
Abstract: Networks which are lacking in uninterrupted back-to-back links amongst their nodes due to node movement, controlled power sources or restricted data storage space are called DTNs. To rise above this irregular connectivity, DTN nodes stock up and hold the data packets they accept until they come into communication range of each other. In addition, they extend many copies of the same packet on the network to increase the deliverance prospect. In recent time, several routing protocols have been developed specifically for DTNs. These protocols differ in the number of copies they extend and the information they use to guide the packets to their destinations. This paper studies four recognized DTN routing protocols i.e. EPIDEMIC, Spray-and-Wait, PROPHET and MAXPROP. In this paper, DTN is studied along with its protocols and measured in environment of packet deliverance, delivery cost and average packet delay and finally finding out the best protocol under certain networking parameters.